A contribuição dos Programas Oficiais para a Consolidação Sócio-Espacial de assentamentos informais: uma avaliação do Plano de Desenvolvimento Local nos assentamentos do Riacho Doce e Pantanal Belém/PA - NEGRÃO, Marcília Regina Gama (Universidade Federal do Pará, 2011)
This work presents a fulfilled investigation with the inhabitants of the two produced sittings informally in a area belongs to municipal public power and federal government in Belém, known Riacho Doce and Pantanal, about the resulting impact of the implantation in the area of a physics improvement project to enable population, known Local Development Program, financed by Habitar Brasil BID program. The research identified economic-social aspects, occurred modifications in the habitation, beyond to fulfill the estimate about the directrixes of the project where we can identify five resident groups (no removed , in removing, removed, indemnified, the resident of a sitting in formation) all established after of the intra-domicile social-economic profile, and their relative localization in the sitting. The plain impacts were too various, the resident with accumulated experience greater in the process type, and those that werent removed were the more beneficed. Between removed detach the satisfaction with the physics improvement, and through in removing and seated new observe the limitations of the process, recurrent of change in the municipal management, and of the disarticulation of the PDL with sectorial politics applicable to theme.